Fitotoxicidade de herbicidas pós-emergentes em híbridos de milho - Portugal, Leandro Vilela (2012)
In corn crop, postemergence herbicides have been widely used because of its efficacy, convenience and cost feasibility. The objective of this study was to evaluate the phytotoxicity of herbicides used in post-emergence, and their interference in the productivity of corn hybrids. The experiment was conducted at the Federal Institute of Education, Science and Technology IFSULDEMINAS, campus Machado. Was used a randomized block experimental design (RBD) with 6 treatments and 4 repetitions, totaling 24 plots. For this, were used two hybrids with similar size and characteristics: Hybrid 1 VT PRO 1 and hybrid 2 VT PRO 2. The hybrid 1 presents the transgenic event of resistance to fall armyworm (Spodoptera frugiperda) and the hybrid 2 shows the same transgenic event of resistance to fall armyworm (Spodoptera frugiperda) and to roundup, called Roundup Ready (RR). Were used six different treatments in hybrids, in the hybrid VT PRO 1 with resistance to fall armyworm were applied herbicides, atrazine + tembotrione (triazines + benzoilciclohexanodiona); nicosulfuron + atrazine (triazines + sulfonylurea); mesotrione + atrazine (triazines + tricetonas) and control treatment where no herbicide was applied. For the hybrid VT PRO 2 with resistance to fall armyworm and the roundup was applied herbicide atrazine + glyphosate (triazines + substituted glycine) and control treatment without herbicide application. Treatments were weeded manually during all the experiment conduction. There was incidence of lightweight phytotoxicity with leaf lesions below 7%, which reduced up to 28 DAA. The combination of atrazine with tembotrione or nicosulfuron reduced corn productivity in 1.066 and 1.122 kg ha-1 respectively. The application of atrazine + mesotrione in hybrid VT PRO 1 and glyphosate in hybrid VT PRO 2, compare to their control treatments, did not affect production. However, the productivity in the hybrid VT PRO 1 was greater than the hybrid VT PRO 2, a result which was not expected to equal hybrids with different events. It was observed in all treatments productivity above 10 tonnes ha-1. The combination of herbicides leads to the emergence of phytotoxicity minor injuries; Atrazine in combination with tembotrione or nicosulfuron reduces corn productivity.